Cisplatin and radiation therapy in HIV-positive women with locally advanced cervical cancer in sub-Saharan Africa: A phase II study of the AIDS malignancy consortium - Einstein, Mark H.; Ndlovu, Ntokozo; Lee, Jeannette; Stier, Elizabeth A.; Kotzen, Jeffrey; Garg, Madhur; Whitney, Kathleen; Lensing, Shelly Y.; Tunmer, Mariza; Kadzatsa, Webster; Palefsky, Joel; Krown, Susan E. (Gynecologic oncology, 2019)
To determine the feasibility, safety, and tolerability of concomitant chemoradiotherapy administered at standard doses in HIV-infected women with locally-advanced cervical cancer (LACC) receiving antiretroviral therapy (ART). Eligible participants had HIV infection and untreated, histologically-confirmed, invasive carcinoma of the uterine cervix, FIGO stages IB2, IIA (if tumor >4 cm), IIB, IIIA, IIIB, or IVA and met standard eligibility criteria. Subjects were prescribed 41.4–45 Gy external beam radiation therapy followed by high dose rate brachytherapy concomitant with up to six weekly doses of cisplatin 40 mg/m2 and were followed for 12 months. Sixty-four women were screened at two sites in sub-Saharan Africa, of whom 40 eligible participants were enrolled, for a screening ratio of 1.60. Of the 38 eligible participants who initiated study treatment, 31 (82%) completed treatment. By the 12-month follow-up visit, 7 women had died of disease and 29 of 31 (94%) returned for follow-up. One-year progression-free survival was 76.3% (95% CI, 59.4–86.9%), and did not significantly differ according to stage at entry (p = 0.581). Participant-reported adherence to ART was high; by 12 months, 93% of participants had an undetectable viral load. The most common grade 3 or 4 adverse event was decreased lymphocyte count that affected all treated participants. Non-hematologic serious adverse events were similar to those observed in women with LACC without HIV infection. The majority of HIV-infected women with LACC can complete concomitant chemoradiotherapy with the same cisplatin dose used in HIV-uninfected women with comparable tolerability and high ART adherence while on treatment. •HIV-infected women with advanced cervical cancer on ART tolerate concomitant chemoradiotherapy•Most HIV+ women with cervical cancer on ART complete all prescribed cycles of radiosensitizing chemotherapy at standard dose•1 year PFS of HIV+ women with advanced cervical cancer on ART are similar to their HIV-negative counterparts.•Hematologic toxicities from this standard dosing in this patient population is mostly self-limiting and manageable.